(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The relevance of the topic is also due to the need to improve the educational and training process to prevent overload, injuries, and foster sustainable motivation for sports. Among modern approaches, special attention should be given to the analysis of physical training of children and adolescents, considering sensitive periods, which is key to the effective and safe formation of motor skills and the development of physical qualities at different ages. The purpose of the article is to study and discuss modern approaches to the physical training of children and adolescents in sports. The analysis of positive practices regarding modern approaches to physical training of children and adolescents in sports confirms the need for a comprehensive, integrated, and adaptive approach to the development of children’s and youth sports, where the key factors are interdisciplinary training, social interaction, individualization of the training process, and the introduction of modern methods of assessment and development of physical qualities. In general, modern scientific approaches to the physical training of children and adolescents demonstrate that the most effective programs are those that comprehensively consider age, gender, health status, fitness level, and interests of the child, integrating traditional and modern techniques, including biomechanical analysis, functional monitoring, and self-control. Thus, the systematization of research results suggests that the future of physical training for children and adolescents should be based on the principles of individualization, scientific validity, innovation, and continuous improvement of the professional competence of specialists in the field of physical culture and sports. Physical training for children and adolescents should be planned with consideration of sensitive periods to maximize efficiency and avoid overload. This approach not only allows for better development of physical qualities but also fosters a positive attitude toward physical activity for life. In modern conditions, the decline in physical activity among children and adolescents necessitates the improvement of approaches to their physical training. Particular attention should be paid to age and individual characteristics, sensitive periods of development, and the integration of innovative training methods. An integrated approach that combines physical culture, health, educational, and sports aspects plays an important role in the physical training of young people. A special role is played by the professional competence of the trainer, which includes pedagogical, psychological, medical and biological, and innovative knowledge. Individualized training programs are a key factor in effectiveness. They should consider the level of physical fitness, psycho-emotional state, physiological characteristics, and sports experience of each child. Testing and monitoring the physical condition of young athletes should be carried out systematically and comprehensively. This enables an objective assessment of achievements and planning of workloads according to the athletes’ capabilities. The integration of modern tools, such as biomechanical analysis, self-monitoring technologies, and digital monitoring, is an important factor in improving the efficiency of the training process. The system of selection and training in children’s and youth sports requires further development, particularly considering the specifics of each sport. Analytical analysis demonstrates the necessity of an integrated approach to the physical training of children and adolescents in sports through scientifically grounded, adaptive, and technological methods that ensure both the effectiveness of the training process and the preservation of the younger generation’s health.